Feminist Theories of Agency and Emotion in Academia: A Feminist Historical Materialist Reading - Rebecca Lund (Sociologica)
Higher education, academic work, and gender relations in academia have, as a result of higher education reforms over the past three decades, become increasingly defined by capitalist logics and purposes. My empirical investigations of gender in academia for the past decade have, to a large extent, drawn on Institutional Ethnography, a method-of-inquiry developed by Marxist feminist sociologist, Dorothy Smith. This method-of-inquiry has largely oriented me towards the language-driven social coordination of academic work as this has been shaped in the context of academic capitalism and neoliberal higher education reforms. However, these explorations revealed complexities in the dynamics of compliance, buying into and resisting the social organisation of academia, which called for a theorisation of emotion. This essay, starting from an account of my historical materialist ontological and epistemological premises, explores and evaluates three approaches to agency and emotion: (1) Feminist Governmentality, (2) Feminist New Materialism, and (3) Feminist Practice Theory. I argue that a feminist practice theoretical conception of agency and emotion is most coherent with the historical materialist premises and the anti-ideological purposes of Institutional Ethnography.